2011
DOI: 10.1051/0004-6361/201117384
|View full text |Cite
|
Sign up to set email alerts
|

One blind and three targeted searches for (sub)millisecond pulsars

Abstract: Context. Millisecond pulsars are very useful for determining the properties of neutron stars, for testing General Relativity and for detecting gravitational waves. However, the number of known millisecond pulsars is very small compared to that of ordinary pulsars. Aims. We conducted one blind and three targeted searches for millisecond and submillisecond pulsars at radio frequencies. Methods. The blind search was conducted within 3 • of the Galactic plane and at longitudes between 20 • and 110 • . It takes 22 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Spin frequency cutoff. Even though theoretical models of NSs allow for spin rotation rates much above 1 kHz and although with current observational techniques such rapidly rotating pulsars could be detected (see, e.g., Patruno 2010;Davoust et al 2011), so far, the most rapidly rotating NS observed is PSR J1748-2446ad (716 Hz, Hessels et al 2006). It cannot be excluded a priori that some rapidly rotating and massive NSs were created close to their currently observed state, that is, in a specific type of core-collapse supernovae.…”
Section: Discussionmentioning
confidence: 99%
“…Spin frequency cutoff. Even though theoretical models of NSs allow for spin rotation rates much above 1 kHz and although with current observational techniques such rapidly rotating pulsars could be detected (see, e.g., Patruno 2010;Davoust et al 2011), so far, the most rapidly rotating NS observed is PSR J1748-2446ad (716 Hz, Hessels et al 2006). It cannot be excluded a priori that some rapidly rotating and massive NSs were created close to their currently observed state, that is, in a specific type of core-collapse supernovae.…”
Section: Discussionmentioning
confidence: 99%
“…When they selected all sources with α < −1.6 and examined the distribution of as a function of galactic latitude b they saw an excess in the fraction of steep-spectrum sources near the galactic plane (|b| < 15 • ) and suggested that these may be previously unknown pulsars. Davoust, Petit & Fayard (2011) searched for pulsations at 1.4 GHz using a sub-sample of 24 unresolved candidates with a polarised intensity (at 1.4 GHz) of ≥ 5 per cent. No pulsars were found.…”
Section: An Excess Of Steep-spectrum Sources On the Galactic Planementioning
confidence: 99%
“…Although with current observational techniques submillisecond pulsars could in principle be detected, so far all attempts were unsuccessful (see, e.g., [40][41][42]). Thus this might indicate the existence of a mechanism that 2 http://www.atnf.csiro.au/people/pulsar/psrcat.…”
Section: Spin Frequencymentioning
confidence: 99%